"Better to be a pessimist": A narrative inquiry into mathematics teachers' experience of the transition to the Common Core. Issue 6 (1st November 2016) - Martinie, Sherri L.; Kim, Jeong-Hee; Abernathy, Deborah
Abstract: The Common Core State Standards (CCSS) are a focus of state education policy today influencing curriculum implementation and assessment in public schools. The purpose of this narrative inquiry is to understand how high school mathematics teachers experience the transition period. Based on interviews with mathematics teachers in a high school in the Midwest, we aim at bringing teachers' voices to the forefront. Through teachers' stories, we find that: a) Teachers live in the different zones of enactment; and b) Teachers' ecological view of agency should be used as a link to a transition to the CCSS for creating a genuine dialogue. This article is significant in two ways. First, it informs the administrators and policy makers of how there will be inconsistencies across states, districts, schools and classrooms in the implementation and assessment, and second, it helps to explain the need for new professional development approaches.